Hubungan Pengetahuan dengan Sikap Masyarakat pada Penggunaan Antibiotik di Kelurahan Bumi Ayu Kota Bengkulu - Defi Suryanti; Oky Hermansyah; Putri Mulia; Tri Danang Kurniawan; Dwi Dominica (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Irrational use of antibiotics in the community remains a health problem that can increase the risk of antimicrobial resistance, Low levels of public knowledge are suspected to influence the formation of inappropriate attitudes toward antibiotic use. This study aimed to analyze the relationship between the level of knowledge and community attitudes toward antibiotic use in Bumi Ayu Village, Bengkulu City. This study used a quantitative method with an observational analytic design through a cross-sectional approach. The sample consisted of 110 respondents selected using a proportional cluster random sampling technique. Data were collected using questionnaires that had been tested for validity and reliability, with Cronbach’s Alpha values of 0.702 for the knowledge variable and 0.786 for the attitude variable. Data were analyzed using univariate and bivariate analyses with the Chi-Square test. The results showed that most respondents had low knowledge levels, with 50 respondents (45.5%), and poor attitudes, with 50 respondents (45.5%). The bivariate analysis showed a significant relationship between the level of knowledge and community attitudes toward antibiotic use, with a p-value of 0.000 (p < 0.05). Respondents with better knowledge tended to have better attitudes toward antibiotic use. Therefore, continuous health education through health workers and information media is needed to improve public understanding of rational antibiotic use in order to prevent antimicrobial resistance.